![y=x^r](https://tex.z-dn.net/?f=y%3Dx%5Er)
![\implies r(r-1)x^r+6rx^r+4x^r=0](https://tex.z-dn.net/?f=%5Cimplies%20r%28r-1%29x%5Er%2B6rx%5Er%2B4x%5Er%3D0)
![\implies r^2+5r+4=(r+1)(r+4)=0](https://tex.z-dn.net/?f=%5Cimplies%20r%5E2%2B5r%2B4%3D%28r%2B1%29%28r%2B4%29%3D0)
![\implies r=-1,r=-4](https://tex.z-dn.net/?f=%5Cimplies%20r%3D-1%2Cr%3D-4)
so the characteristic solution is
![y_c=\dfrac{C_1}x+\dfrac{C_2}{x^4}](https://tex.z-dn.net/?f=y_c%3D%5Cdfrac%7BC_1%7Dx%2B%5Cdfrac%7BC_2%7D%7Bx%5E4%7D)
As a guess for the particular solution, let's back up a bit. The reason the choice of
![y=x^r](https://tex.z-dn.net/?f=y%3Dx%5Er)
works for the characteristic solution is that, in the background, we're employing the substitution
![t=\ln x](https://tex.z-dn.net/?f=t%3D%5Cln%20x)
, so that
![y(x)](https://tex.z-dn.net/?f=y%28x%29)
is getting replaced with a new function
![z(t)](https://tex.z-dn.net/?f=z%28t%29)
. Differentiating yields
![\dfrac{\mathrm dy}{\mathrm dx}=\dfrac1x\dfrac{\mathrm dz}{\mathrm dt}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cmathrm%20dy%7D%7B%5Cmathrm%20dx%7D%3D%5Cdfrac1x%5Cdfrac%7B%5Cmathrm%20dz%7D%7B%5Cmathrm%20dt%7D)
![\dfrac{\mathrm d^2y}{\mathrm dx^2}=\dfrac1{x^2}\left(\dfrac{\mathrm d^2z}{\mathrm dt^2}-\dfrac{\mathrm dz}{\mathrm dt}\right)](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cmathrm%20d%5E2y%7D%7B%5Cmathrm%20dx%5E2%7D%3D%5Cdfrac1%7Bx%5E2%7D%5Cleft%28%5Cdfrac%7B%5Cmathrm%20d%5E2z%7D%7B%5Cmathrm%20dt%5E2%7D-%5Cdfrac%7B%5Cmathrm%20dz%7D%7B%5Cmathrm%20dt%7D%5Cright%29)
Now the ODE in terms of
![t](https://tex.z-dn.net/?f=t)
is linear with constant coefficients, since the coefficients
![x^2](https://tex.z-dn.net/?f=x%5E2)
and
![x](https://tex.z-dn.net/?f=x)
will cancel, resulting in the ODE
![\dfrac{\mathrm d^2z}{\mathrm dt^2}+5\dfrac{\mathrm dz}{\mathrm dt}+4z=e^{2t}\sin e^t](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cmathrm%20d%5E2z%7D%7B%5Cmathrm%20dt%5E2%7D%2B5%5Cdfrac%7B%5Cmathrm%20dz%7D%7B%5Cmathrm%20dt%7D%2B4z%3De%5E%7B2t%7D%5Csin%20e%5Et)
Of coursesin, the characteristic equation will be
![r^2+6r+4=0](https://tex.z-dn.net/?f=r%5E2%2B6r%2B4%3D0)
, which leads to solutions
![C_1e^{-t}+C_2e^{-4t}=C_1x^{-1}+C_2x^{-4}](https://tex.z-dn.net/?f=C_1e%5E%7B-t%7D%2BC_2e%5E%7B-4t%7D%3DC_1x%5E%7B-1%7D%2BC_2x%5E%7B-4%7D)
, as before.
Now that we have two linearly independent solutions, we can easily find more via variation of parameters. If
![z_1,z_2](https://tex.z-dn.net/?f=z_1%2Cz_2)
are the solutions to the characteristic equation of the ODE in terms of
![z](https://tex.z-dn.net/?f=z)
, then we can find another of the form
![z_p=u_1z_1+u_2z_2](https://tex.z-dn.net/?f=z_p%3Du_1z_1%2Bu_2z_2)
where
![u_1=-\displaystyle\int\frac{z_2e^{2t}\sin e^t}{W(z_1,z_2)}\,\mathrm dt](https://tex.z-dn.net/?f=u_1%3D-%5Cdisplaystyle%5Cint%5Cfrac%7Bz_2e%5E%7B2t%7D%5Csin%20e%5Et%7D%7BW%28z_1%2Cz_2%29%7D%5C%2C%5Cmathrm%20dt)
![u_2=\displaystyle\int\frac{z_1e^{2t}\sin e^t}{W(z_1,z_2)}\,\mathrm dt](https://tex.z-dn.net/?f=u_2%3D%5Cdisplaystyle%5Cint%5Cfrac%7Bz_1e%5E%7B2t%7D%5Csin%20e%5Et%7D%7BW%28z_1%2Cz_2%29%7D%5C%2C%5Cmathrm%20dt)
where
![W(z_1,z_2)](https://tex.z-dn.net/?f=W%28z_1%2Cz_2%29)
is the Wronskian of the two characteristic solutions. We have
![u_1=-\displaystyle\int\frac{e^{-2t}\sin e^t}{-3e^{-5t}}\,\mathrm dt](https://tex.z-dn.net/?f=u_1%3D-%5Cdisplaystyle%5Cint%5Cfrac%7Be%5E%7B-2t%7D%5Csin%20e%5Et%7D%7B-3e%5E%7B-5t%7D%7D%5C%2C%5Cmathrm%20dt)
![u_1=\dfrac23(1-2e^{2t})\cos e^t+\dfrac23e^t\sin e^t](https://tex.z-dn.net/?f=u_1%3D%5Cdfrac23%281-2e%5E%7B2t%7D%29%5Ccos%20e%5Et%2B%5Cdfrac23e%5Et%5Csin%20e%5Et)
![u_2=\displaystyle\int\frac{e^t\sin e^t}{-3e^{-5t}}\,\mathrm dt](https://tex.z-dn.net/?f=u_2%3D%5Cdisplaystyle%5Cint%5Cfrac%7Be%5Et%5Csin%20e%5Et%7D%7B-3e%5E%7B-5t%7D%7D%5C%2C%5Cmathrm%20dt)
![u_2=\dfrac13(120-20e^{2t}+e^{4t})e^t\cos e^t-\dfrac13(120-60e^{2t}+5e^{4t})\sin e^t](https://tex.z-dn.net/?f=u_2%3D%5Cdfrac13%28120-20e%5E%7B2t%7D%2Be%5E%7B4t%7D%29e%5Et%5Ccos%20e%5Et-%5Cdfrac13%28120-60e%5E%7B2t%7D%2B5e%5E%7B4t%7D%29%5Csin%20e%5Et)
![\implies z_p=u_1z_1+u_2z_2](https://tex.z-dn.net/?f=%5Cimplies%20z_p%3Du_1z_1%2Bu_2z_2)
![\implies z_p=(40e^{-4t}-6)e^{-t}\cos e^t-(1-20e^{-2t}+40e^{-4t})\sin e^t](https://tex.z-dn.net/?f=%5Cimplies%20z_p%3D%2840e%5E%7B-4t%7D-6%29e%5E%7B-t%7D%5Ccos%20e%5Et-%281-20e%5E%7B-2t%7D%2B40e%5E%7B-4t%7D%29%5Csin%20e%5Et)
and recalling that
![t=\ln x\iff e^t=x](https://tex.z-dn.net/?f=t%3D%5Cln%20x%5Ciff%20e%5Et%3Dx)
, we have